2022
DOI: 10.1186/s40981-021-00485-1
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of difficulty in achieving definitive loss of consciousness with remimazolam

Abstract: Background Remimazolam is a novel, ultra-short-acting benzodiazepine used for general anesthesia. Because remimazolam is an emerging drug, the tolerance to remimazolam in benzodiazepine-taking patients has been unclear. Also, the efficacy of remimazolam in different races is not fully elucidated so far. Case presentation Here we experienced three cases in which high dose of remimazolam was needed for attempting to achieve appropriate anesthetic dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that remimazolam-based TIVA can lead to elevated PSI values compared with propofol-based TIVA, with some values exceeding the threshold of 50 [ 16 , 37 ]. Additionally, there have been reports of chronic benzodiazepine users developing tolerance to remimazolam, necessitating the use of alternative anesthetics or higher remimazolam dosages [ 38 , 39 ]. Although our study included chronic benzodiazepine users, we did not observe any such discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that remimazolam-based TIVA can lead to elevated PSI values compared with propofol-based TIVA, with some values exceeding the threshold of 50 [ 16 , 37 ]. Additionally, there have been reports of chronic benzodiazepine users developing tolerance to remimazolam, necessitating the use of alternative anesthetics or higher remimazolam dosages [ 38 , 39 ]. Although our study included chronic benzodiazepine users, we did not observe any such discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…However, when remimazolam is administered externally at the approved maximum infusion rate, the BIS value should be maintained ˂ 60 regardless of endozepines levels. In a case report, two patients receiving benzodiazepines before surgery required large doses of remimazolam to achieve a BIS of less than 60 27 . This suggests that the patient’s concomitant medications may affect intraoperative BIS values.…”
Section: Discussionmentioning
confidence: 99%
“…This case report demonstrates that dc-MEP recording under remimazolam Remimazolam has some issues that should be addressed. First, the reliability of frontal EEG-derived index alteration is still controversial [21], despite the good correlations between the BIS value, and the effects of propofol, midazolam, and isoflurane on the level of consciousness and recall were evident [22]. The EEG effects of benzodiazepines are predominantly a monotonic beta activation, especially in frontal areas, and these effects map to higher EEG-derived indices to estimate the anesthesia depth [23].…”
Section: Discussionmentioning
confidence: 99%